Acoustical Comparison between /u/ and /u:/ Arabic Vowels for Non-Native Speakers - Ali Abd Almisreb; Nooritawati Md Tahir; Ahmad Farid Abidin; Norashidah Md Din (Institute of Advanced Engineering and Science, 2018)
The articulation of Arabic phonemes is essential for the Malay community since Arabic language is mandatory to perform worship. Hence, in this paper, an acoustical analysis of Arabic phonemes for vowels /u/ and /u:/ is discussed based on tokens pronounced by Malay speakers. The experimental results showed that the Malay speakers are inclined to utter these Arabic phonemes similar to the native speakers and it was also found from the analysis that the vowel /u/ and /u: was articulated as high-back vowels. Conversely, the vowel /u/ was located lower than /u:/ as in the vowel-space. Alternatively results also showed that /u/ and /u:/ is higher than the other vowels specifically /a/ and /a:/. In addition, the statistical analysis showed that the formant frequencies of both short and long dummah for formant frequency F1, F2 and F3 have more variation in terms of /u/ as compare to /u:/. In contrast formant frequency F4 and F5 are more diversity in terms of /u:/.